Morisprudence: a theoretical framework for studying the relationship linking moral case deliberation, organisational learning and quality improvement - Kok, Niek (Journal of medical ethics, 2022)
There is a claim that clinical ethics support services (CESS) improve healthcare quality within healthcare organisations. However, there is lack of strong evidence supporting this claim. Rather, the current focus is on the quality of CESS themselves or on individual learning outcomes. In response, this article proposes a theoretical framework leading to empirical hypotheses that describe the relationship between a specific type of CESS, moral case deliberation and the quality of care at the organisational level. We combine insights from the literature on CESS, organisational learning and quality improvement and argue that moral case deliberation causes healthcare professionals to acquire practical wisdom. At the organisational level, where improving quality is a continuous and collective endeavour, this practical wisdom can be aggregated into morisprudence, which is an ongoing formulation of moral judgements across cases encountered within the organisation. Focusing on the development of morisprudence enables refined scrutinisation of CESS-related quality claims.